2020
DOI: 10.32598/jhnm.30.3.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Self-efficacy and Health-Promoting Lifestyle in Students

Abstract: Health-promoting lifestyle is an important determinant of health status and has been identified as a major factor in maintaining and promoting health. Self-efficacy is a psychosocial factor that promotes health. Objective: This study aimed to determine the relationship between self-efficacy and healthpromoting lifestyles in students. Materials and Methods: The present study is a cross-sectional analysis. The research population included all students studying at universities in Zanjan City, Iran. The sampling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the literature, it has been determined in some studies that healthy lifestyle behavior levels do not differ according to gender (Cihangiroğlu & Deveci, 2011;Abbasi et al, 2020). In the study, no significant change was found between healthy lifestyle behaviors and gender factors.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…In the literature, it has been determined in some studies that healthy lifestyle behavior levels do not differ according to gender (Cihangiroğlu & Deveci, 2011;Abbasi et al, 2020). In the study, no significant change was found between healthy lifestyle behaviors and gender factors.…”
Section: Discussionmentioning
confidence: 71%
“…With the acquisition of accurate and objective information about healthy living behaviors in society, lifestyles that support healthy life can exist. In particular, individual lifestyles emerge with the construction of valuable healthy structures (Abbasi, 2020;Ahmadi & Roosta, 2015;Davis & De Guzman, 2022;Lopes Sousa et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1 Respiratory complications of mustard gas exposure include tracheal stenosis, tracheomalacia, bronchiectasis and constrictive bronchiolitis 2–4 leading to cough, sputum and breathlessness, associated with limitation of exercise capacity and difficulties with day to day activities. As is the case with other long-term respiratory conditions, 5 fatigue anxiety and depression are also common 6 7 while clinical symptoms and quality of life are only poorly correlated with measures of lung function. 8 The clinical picture is thus similar to that observed in chronic obstructive pulmonary disease (COPD).…”
Section: Introductionmentioning
confidence: 96%
“…[ 1 ] Iran has a high prevalence of preterm neonate with a premature birth rate of 12% per year. [ 2 ]…”
Section: Introductionmentioning
confidence: 99%